Impact of Quantisal® Oral Fluid Collection Device on Drug Stability - Riggio, Michela; Dave, Keyur A.; Koscak, Branko; Blakey, Mark; Appleton, Charles (Frontiers in Toxicology, 2021)
Stability of drugs can affect drug tests and interpretations. A comprehensive study to verify drug stability in Quantisal® oral fluid collection device was undertaken in accordance with Australian standard, AS/NZS 4760:2019 (SAI-Global, 2019). The evaluation was performed for the following drugs: (_) amphetamine, (_) methamphetamine, (_) 3,4-methylenedioxymethamphetamine(MDMA), (±)-9-tetrahydrocannabinol (THC), cocaine, benzoylecgonine, morphine, codeine, and oxycodone. Stability was assessed at four different storage temperatures over seven time points at _50% cut-off concentrations (Appendix A, Para A4-4.1, AS/NZS 4760:2019) (SAI-Global, 2019). All drugs were found to be significantly more stable at 4°C and -20°C, with stability spanning at least fourteen days with percent change from the cut-off concentrations (SAI-Global, 2019) within ±20%. In addition, we report a variation trend with cocaine and benzoylecgonine at elevated temperatures suggesting hydrolytic decomposition of cocaine and concomitant increase in benzoylecgonine quantitative values. We confirm the crosstalk by showing that the percent change profile of average cocaine-benzoylecgonine measurement is within the acceptance concentration range of 20%. This finding highlights the importance of precaution during storage and careful considerations during subsequent interpretation of liquid chromatography-mass spectrometry (LCMS) measurements.